NON-CLINICAL DEVELOPMENT OF CER-001 - Ronald eBarbaras (Frontiers Media S.A., 2015)
Cardiovascular disease remains the most pressing healthcare issue for the developed world and is becoming so for developing countries. There are no currently approved therapies that can rapidly reduce the burden of unstable, inflamed plaque in the overall coronary vascular bed. High-density lipoprotein (HDL) has multiple actions that could lead to plaque stabilisation, such as rapid removal of large quantities of cholesterol from the vasculature through the process of reverse lipid transport (RLT), improvement in endothelial function, protection against oxidative damage and reduction in inflammation. Short-term infusion of HDL-mimetics in animal models as well as in humans has shown promising effects on the plaque size and morphology. Cerenis Therapeutics has developed CER-001, a negatively charged lipoprotein complex consisting of phospholipid and recombinant human apoA-I that mimics the structure and function of natural HDL. Three clinical trials using CER-001 infusions have demonstrated improvements in the carotid wall thickness of patients with familial hypercholesterolaemia and in patients with hypo-alphalipoproteinaemia, as well as an impact on coronary plaque burden measured by IVUS at the lowest tested dose (3 mg/kg) in post-ACS patients. Here, we reviewed the non-clinical data leading to the demonstration that CER-001 is a full HDL mimetic.